Self-Esteem, Study Habits and Academic Performance Among University Students - Chilca Alva, Manuel L. (2017)
This study was intended to establish whether self-esteem and study habits correlate with academic performance among university students. Research conducted was descriptive observational, multivariate or cross-sectional factorial in nature. The study population consisted of 196 students enrolled in a Basic Mathematics 1 class at the School of Engineering of Universidad Tecnológica del Perú (Technical University of Peru, UTP) in the third term of 2016, and the sample size numbered 86 students. The Coopersmith Self-Esteem Inventory, Luis Vicuña Peri’s Study Habits Inventory and the average grades obtained by students were used for research variable measurement. Results show that self-esteem does not significantly impact academic performance, but study habits do influence academic performance (p = .000 <α = .05). Hence students are expected to enhance academic performance as they refine study techniques.